The Effects of Powtoon on Form 2 Pupils’ Understanding of Poems - Hua, Ting Suk; Mohamad, Maslawati (Opción, 2019)
This study was conducted to identify the effects of PowToon on Form 2 pupils’ understanding of poems and pupils’ perceptions on the use of PowToon in improving their comprehension of poems. This case study involved six Form 2 pupils from a secondary school in Bintangor. The research instruments were document analysis, focus-group interview, reflective journals, questionnaire and field note. The results showed that PowToon is able to enhance Form 2 pupils’ understanding of poems, ease the process of understanding and have better engagement. Besides, participants of the study perceive PowToon as a learning tool that is attractive to be used.